'Meet and greet' intake appointments in primary care: a new pattern of patient intakes?. (9th May 2017) - Marshall, Emily Gard; Ogah, Imhokhai; Lawson, Beverley; Gibson, Richard J; Burge, Frederick
Abstract: Background: Family physicians (FPs) are expected to take on new patients fairly and equitably and to not discriminate based on medical or social history. 'Meet and greet' appointments are initial meetings between physicians and prospective patients to establish fit between patient needs and provider scope of practice. The public often views these appointments as discriminatory; however, there is no empirical evidence regarding their prevalence or outcomes. Objectives: To determine the proportion of FPs conducting 'meet and greets' and their outcomes. Methods: Study design and setting : Census telephone survey of all FP practices in Nova Scotia (NS). Participants : Person who answers the FP office telephone. Main Outcomes : Proportion of FPs holding 'meet and greets'; proportion of FPs conducting 'meet and greets' who have ever decided not to continue seeing a patient after the meeting. Results: 9.2% of FPs accept new patients unconditionally; 51.1% accept new patients under certain conditions. Of those accepting patients unconditionally or with conditions, 46.9% require a 'meet and greet'; 41.8% have a first-come, first-serve policy. Among FPs who require a 'meet and greet', 44.0% decided, at least once, not to continue seeing a patient after the first meeting. Conclusion: 'Meet and greets' are common among FPs in NS and result in some patients not being accepted into practice. More research is needed to understand the intentions, processes, and outcomes of 'meet and greets'. We recommend that practice scope be made clear to prospective patients before their first visit, which may eliminate the need for 'meet and greets'.